Erroneous Production of Apico-Dental Fricative Consonant Sounds by Javenese School Students - Afrinta Puspandari (Lexicon, 2013)
This research paper aims to investigate the errors in the production of apico-dental fricative consonant sounds by Javanese high school students. Particularly, it attempts to investigate deviation and the different intensity level in producing apico-dental fricative sounds such as [θ] and [ð]. The data used in this research were 30 words containing apico-dental fricatives in initial, medial, and final positions. The results of the research show that the range intensity level between Oxford Advanced Learner’s Dictionary (OALD) and English learners is different. In initial position, the production of [θ] sound has range 52.92 dB – 59.60 dB while the deviations are at 65.83 dB – 70.98 dB; in the middle is 78.94 dB – 79.87 dB while the deviations are at 74.74 dB – 76.03 dB; in final position the range is at 85.73 dB – 88.52 dB while the deviations are at 72.81 dB – 77.35 dB. In the production of [ð] sound, the range in initial position is 61.6 dB- 62.33 dB while the deviations are at 76.47 dB – 82.08 dB; in medial position the range is 81.64 dB – 84.23 dB while the deviations occurred at 70.81 dB – 75.97 dB; in final position the range is 81.95 dB – 83.21 dB while the deviations occurred at 74.27 dB -79.98 dB. In the pronunciation process, there are seven possible errors, namely [t], [tʰ], [tʃ], [s], the deletion of [θ], [d], and [nd].